Hemodynamic Changes in Umbilical Artery and Middle Cerebral Artery With Oligohydramnios in Third Trimester of Pregnancy. (March 2022) - Jabeen, Zara; Bacha, Raham; Zain-ul-Hassan,; Fatima, Mehreen; Manzoor, Iqra; Ramzan, Iqra; Iyaz, Maida
Objective: The objective of this study was to determine the hemodynamic changes in the umbilical artery (UA) and middle cerebral artery (MCA) with oligohydramnios, during third trimester of pregnancy. Materials and Methods: A cross-sectional descriptive study was done in a perinatal ultrasound center, over a 9-month period. The participant sample size was 64, and all of the women were conveniently consented and selected for the study. All individuals were referred for obstetrical sonography in the third trimester, with oligohydramnios. All fetal anomalies, such as a neural tube defect, dwarfism, an abdominal wall defect, were excluded from the study. Results: The mean systolic to diastolic (S/D) ratio for the UA was 3.01, within a range of 1.49 to 5.60 (± 0.79 SD). The mean pulsatility index (PI), of the UA, was 1.11, within a range of 0.41 to 5.51 cm (± 0.64 SD). The mean resistive index (RI) of the UA was 0.66, within a range of 0.33 to 1.25 cm (± 0.13 SD). The mean S/D ratio of the MCA was 5.68, within a range of 2.05 to 26.10 (± 3.10 SD). The mean PI of the MCA was 1.67 within a range of 0.75 to 2.55 cm (± 0.45 SD). The mean resistive index (RI), of the UA, was 0.82 within a range of 0.51 to 1.77 cm (± 0.82 SD). Conclusion: The Doppler indices may rise as pregnancy advances, especially in fetuses with oligohydramnios. In these types of patients, the flow within the MCA may decrease, with an increase in the gestational age. Consequently, it appears that oligohydramnios may lead to vascular remodeling of the UA and MCA.